Highly Reversible Zn Metal Anodes Realized by Synergistically Enhancing Ion Migration Kinetics and Regulating Surface Energy. (21st October 2022) - Wang, Yang; Deng, Zheng; Luo, Bin; Duan, Guosheng; Zheng, Sinan; Sun, Leilei; Ye, Zhizhen; Lu, Jianguo; Huang, Jingyun; Lu, Yingying
Abstract: The Zn metal anode suffers from uncontrollable dendrite formation and intricate parasitic reactions that dramatically impede the commercialization of aqueous Zn metal batteries (AZMBs). This st proposes synergistic strategies for facilitating Zn 2+ migration kinetics and regulating surface energy to achieve dendrite‐free Zn deposition and suppressing self‐corrosion by covering Zn anode with multifunctional covalent organic frameworks possessing sulfonate‐rich (SO3 H) covalently‐tethered nanochannels (SCOFs). Benefiting from the vital interplay between SO3 H and Zn 2+, the SCOFs coatings form ample Zn 2+ accelerated transport channels to extract Zn 2+ from the electrolyte quickly, thereby promoting rapid desolvation of hydrated Zn 2+, enhancing ion replenishment capability, and guaranteeing a steady stream of Zn 2+ flux for endowing uniform and compact nucleation. Additionally, the zincophilic SCOFs significantly reduce the surface energy of the Zn (002) crystal plane, inducing preferentially crystallographic (002) orientation electroplating growth. Consequently, the SCOFs‐coated Zn anodes (SCOFs@Zn) demonstrate an excellent lifespan up to 4000 h at 5 mA cm −2, 1 mAh cm −2, and 3000 h at 5 mA cm −2, 2 mAh cm −2 . Meanwhile, the full cell paired with the MnO2 cathode sustains remarkable reversibility within 1000 cycles. The synergistic approach to manipulating ion migration and surface energy provides new insights into developing highly stable AZMBs. Abstract : Through synchronously governing Zn 2+ migration kinetics and regulating Zn (002) surface energy, the reversibility of Zn electroplating is significantly enhanced by coating Zn with sulfonate‐rich covalently‐tethered nanochannels (SCOFs). The as‐designed SCOFs@Zn anode exhibits an impressive lifespan over 4000 h at 5 mA cm −2, 1 mAh cm −2, proving distinguished competitiveness compared with recently reported high‐performance Zn anodes.